The value of culturedness: Bosnian and Hungarian migrants' experiences of belonging in Australia. (2nd September 2015) - Voloder, Lejla; Andits, Petra
Abstract : In this paper we investigate how the values of respect and dignity inform the ways migrants from Bosnia and Herzegovina and Hungary in Australia locate themselves in relation to local, national and transnational identities. Drawing upon ethnographic insights, we discuss how the concept of culturedness is implicated in these migrant claims for dignified belonging. Determinants of culturedness are informed by influential narratives of 'East versus West', 'Balkan versus Europe', the 'New World (Australia) versus the Old World' (Europe). Implicit within these discourses are attempts to demarcate civilisational distinctions. We argue that dignified belonging for people from these migrant communities in Australia involves negotiating identification with culturedness and positioning themselves on the right side of the civilised/primitive divide. This collaboration draws attention to the significance of ontological security through respect within the shared discourses and experiences of belonging for members of these two migrant groups in Australia.